2022
DOI: 10.1186/s12977-022-00603-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human endogenous retroviruses and cytokines expression in peripheral blood mononuclear cells from autistic children and their parents

Abstract: Background Putative pathogenic effects mediated by human endogenous retroviruses (HERVs) in neurological and psychiatric disorders in humans have been extensively described. HERVs may alter the development of the brain by means of several mechanisms, including modulation of gene expression, alteration of DNA stability, and activation of immune system. We recently demonstrated that autistic children and their mothers share high expression levels of some HERVs and cytokines in peripheral blood mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
(119 reference statements)
1
2
0
Order By: Relevance
“…Notably, the study has shown transgenerational inheritance via maternal lineage in mice [198], aligning with the observation that human ASD patients and their mothers share abnormal ERV expression patterns [199]. Most importantly, ERV and cytokine expression in PBMCs from ASD patients and their parents can be modulated upon drug exposure [200]. Given the abovementioned evidence, ERVs hold promise as both biomarker and therapeutic targets for NDDs.…”
Section: Neurodevelopmental Disorderssupporting
confidence: 70%
“…Notably, the study has shown transgenerational inheritance via maternal lineage in mice [198], aligning with the observation that human ASD patients and their mothers share abnormal ERV expression patterns [199]. Most importantly, ERV and cytokine expression in PBMCs from ASD patients and their parents can be modulated upon drug exposure [200]. Given the abovementioned evidence, ERVs hold promise as both biomarker and therapeutic targets for NDDs.…”
Section: Neurodevelopmental Disorderssupporting
confidence: 70%
“…A sex-linked molecular signature comprising ERVs and immune mediators has also been proposed in ASD families, in which only ASD children and their mothers share high levels of expression of some human ERVs and cytokines in peripheral cells, whereas no association was found with fathers. The common expression profile in ASD children and their mothers, and the discrepancy with fathers, support the hypothesis of maternal imprinting as a contributing factor in increasing susceptibility to neurodevelopmental disorders [64,65]. As such, the elevated ERV transcriptional activity in females could be due to the combination of a variety of complex female physiological events (e.g., oogenesis, fertilization, fetal stem cell development, placentation, and pregnancy maintenance) that provide selective pressures on ERV activity [66].…”
Section: Discussionmentioning
confidence: 59%
“…EFV specifically restored the HERV activity with a concomitant modulation of cytokines, in particular lowering the pro-inflammatory while maintaining high regulatory ones. This evidence provided new insights into the potential role of HERVs as biomarkers of ASD and raising the possibility of using HERV expression as a therapeutic target for a tailored approach to patient care [86].…”
Section: Human Endogenous Retroviruses In Neurodevelopmental Disordersmentioning
confidence: 96%
“…Among viruses, the herpesviruses, Hepatitis B virus, the human immunodeficiency virus-1 (HIV-1), Influenza A virus and more recently SARS-CoV-2 have been found able to deregulate HERV activity and although so far, an unequivocal pathogenic cause-effect relationship has not been established, their contribution to the development of viral diseases, including virusassociated tumors, has been suggested [77][78][79][80][81][82][83]. Moreover, several in vitro studies demonstrated that cells express HERVs at high levels in response to stimulation by using lipopolysaccharide or interferon-γ (IFN-γ), cytokines as Interleukine-1β (IL-1β) and tumor necrosis factor-α (TNF-α) or mitogens, such as phytohemagglutinin [84][85][86]. These observations could be due to the fact that HERVs showed various regulatory sequences that have been linked to the transcriptional modulation systems [87].…”
Section: The Activation Of Human Endogenous Retrovirusesmentioning
confidence: 99%